Spirituality and spiritual care in in the context of nursing education in South Africa - Sandhya Chandramohan; Raisuyah Bhagwan (AOSIS, 2015)
Background: In order for nursing education to prepare nurses for holistic patient care, it is critical that educators become more aware of the religious and spiritual dimensions in patien tcare and be able to provide adequate knowledge and skills for nurses to offer spiritually-basedc are in an ethical way. Furthermore, spiritual care is an essential component in the nursing context, as nurses have to care for patients who may often turn to the spiritual dimension to cope and heal. These aspects are important issues to be considered in planning what should be taught as part of spiritual care. Objectives: This paper presents findings from a study on nursing practitioners' views on the role of spiritual care in nursing practice and whether current nursing education has integrated this dimension into teaching. Method: A descriptive survey using a cross-sectional design with 385 nurses was conducted between December 2012 and February 2013. Participants were recruited through multistage random sampling. Data analysis was undertaken using SSPS 0.20. Results: All the participants (n = 385) concurred that spiritual care was a salient component of holistic patient care. They however stated that the primary barriers to providing spiritual care related to uncertainty on how to provide this type of care, and a lack of educational preparedness for this role. Conclusion: The study found that nurses were very accepting of the need for spiritual care as part of their nursing role but that nursing education had not paid adequate attention to integrating this dimension into the nursing curriculum.